Disentangling the avian altricial‐precocial spectrum: Quantitative assessment of developmental mode, phylogenetic signal, and dimensionality. (1st November 2021) - Ducatez, Simon; Field, Daniel J.
Abstract: The altricial‐precocial spectrum describes patterns of variation in avian developmental mode that greatly influence avian life histories. Appraising a given species' position on this spectrum is therefore fundamental to understanding patterns of avian life history evolution. However, evaluating avian developmental mode remains a relatively subjective task reliant on untested assumptions, including the notion that developmental strategies are distributed along a single dimension of statistical variation. Here, we present a quantitative multivariate framework that objectively discriminates among meaningfully different modes of avian development. We gathered information on seven hatchling and post‐hatching traits for up to 4000 extant bird species, and find that most traits related to developmental mode show high phylogenetic signal and little intraclade variation, allowing unknown values to be reliably interpolated. Principal component analyses (PCAs) of these traits illustrate that most variation in hatchling state can be quantified along one dimension of trait space. However, our PCAs also reveal an important second dimension explaining variation in post‐hatching behavior, enabling factors related to hatchling state and post‐hatching behavior to be disentangled. In order to facilitate future macroevolutionary studies of variation in avian developmental strategies, as well as explorations of covariation between developmental mode and other aspects of avian biology, we present PC scores for 9993 extant avian species.